Pathology Imagebase—a reference image database for standardization of pathology. Issue 5 (13th September 2017) - Egevad, Lars; Cheville, John; Evans, Andrew J; Hörnblad, Jonas; Kench, James G; Kristiansen, Glen; Leite, Katia R M; Magi‐Galluzzi, Cristina; Pan, Chin‐Chen; Samaratunga, Hemamali; Srigley, John R; True, Lawrence; et al.
Abstract : Aims: Despite efforts to standardize histopathology practice through the development of guidelines, the interpretation of morphology is still hampered by subjectivity. We here describe Pathology Imagebase, a novel mechanism for establishing an international standard for the interpretation of pathology specimens. Methods and results: The International Society of Urological Pathology (ISUP) established a reference image database through the input of experts in the field. Three panels were formed, one each for prostate, urinary bladder and renal pathology, consisting of 24 international experts. Each of the panel members uploaded microphotographs of cases into a non‐public database. The remaining 23 experts were asked to vote from a multiple‐choice menu. Prior to and while voting, panel members were unable to access the results of voting by the other experts. When a consensus level of at least two‐thirds or 16 votes was reached, cases were automatically transferred to the main database. Consensus was reached in a total of 287 cases across five projects on the grading of prostate, bladder and renal cancer and the classification of renal tumours and flat lesions of the bladder. The full database is available to all ISUP members atwww.isupweb.org . Non‐members may access a selected number of cases. Conclusions: It is anticipated that the database will assist pathologists in calibrating their grading, and will also promote consistency in the diagnosis of difficult cases.